Pregnancy Complications and Neonatal Mortality in a Serotonin Transporter Null Mouse Model: Insight Into the Use of Selective Serotonin Reuptake Inhibitor During Pregnancy - Domingues, Rafael R.; Wiltbank, Milo C.; Hernandez, Laura L. (Frontiers in Medicine, 2022)
Selective serotonin reuptake inhibitors (SSRI) are widely prescribed to pregnant woman. Although some SSRI compounds are known to cause pregnancy loss and fetal malformations, other SSRI continue to be used by pregnant women. However, several studies have associated the use of SSRI with adverse pregnancy outcomes: intrauterine growth restriction, preterm birth, and neonatal morbidity. Nonetheless, interpretation of studies in humans are typically complicated by the adverse pregnancy outcomes caused by depression itself. Therefore, we used a mutant mouse model with genetic ablation of the serotonin transporter, the target site for SSRI, to unravel the role of the serotonin transporter on pregnancy outcomes. Our mouse model recapitulated the occurrence of several adverse pregnancy outcomes similar to those in women undergoing SSRI treatment during gestation: pregnancy loss, preterm birth, fetal malformations, and neonatal morbidity/mortality. Additionally, neonatal loss in the present study reproduced a sudden infant death phenotype as in humans and mice with altered serotonergic signaling. In conclusion, findings from this study demonstrate a role for serotonin transporter in pregnancy maintenance and neonatal health. Additionally, it suggests that the adverse pregnancy outcomes in women taking SSRI during gestation might be due to altered serotonin transporter function caused by SSRI independent of underlying depression. This is a critical finding, given the number of women prescribed SSRI during pregnancy, and provides the framework for critical research in this area.